The Preparation of Eco-Friendly Magnetic Adsorbent from Wild Water Hyacinth (Eichhornia crassipes): The Application for Removing Lead Ions from Industrial Wastewater - Thien Khanh Tran; Quang Dung Le; Thi Muoi Vo; Minh Quang Diep; Thanh Duy Nguyen; Hau Huu Huynh; Quoc Khanh Ly; Namkeun Kim (Adsorption Science & Technology)
Water hyacinth (Eichhornia crassipes) is a wild floating plant that can be found widely in pond or river areas. The plant grows fiercely and causes many harmful issues to the ecosystem around its covered area. This work provides a utilization method that converts wild water hyacinth to reliable magnetic biochar which can be used as a very effective adsorbent for the removal of lead ion Pb(II) in industrial wastewater. The mentioned magnetic biochar can be prepared via a modified pyrolysis process at 550°C with the support of cobalt sulfates as magnetite precursors and limited oxygen from the sweeping gas (the gas mixture ratio is 4 : 1 nitrogen/oxygen). The produced samples were hydrophobic biochar with high oxygen-containing functional groups that are suitable for the removal of inorganic contaminants. The impregnation of cobalt (II, III) oxides provided high magnetic separation performance and additional adsorption sites on the produced magnetic biochar. As indicated by the obtained result, the WHB-Co2M sample possesses a highly porous structure (0.126 cc/g), higher thermal stability (thermal durability reaches 900°C), relatively stable magnetic properties (14.74 emu/g), and a larger surface area (192 m2/g). These beneficial properties led to its suitability to serve as an adsorbent in removing lead ions in the contaminated effluent, recording 95% of removal efficiency and adsorption capacity of 67.815 mg/g. As indicated in the result, all prepared magnetic biochar samples were fitted to two-parameter (Langmuir models) and three-parameter (Sips model) isotherm models. Therefore, the adsorption process in this work could be carried out on both homogeneous and heterogeneous adsorbent surfaces. The adsorption kinetics of the removal process also was described by the pseudo-first-order, pseudo-second-order, and Elovich models to reveal the adsorption and desorption rate of the as-prepared magnetic biochar. This work indicates a successful waste refinery route of converting lignocellulosic biomass such as water hyacinth into value-added material for use as promising heavy metal adsorbents.